KOMPENSASI, KEDISIPLINAN, PENDIDIKAN DAN PELATIHAN SERTA DAMPAKNYA TERHADAP KEPUASAN KERJA PEGAWAI DI RSUD LANDAK - admin, DERATEA MELITA B11111045 (Jurnal Manajemen Update, 2015)
Compensation, discipline, education and training if properly applied by companies will trigger high working spirit and give positive effect on companies profitability and employees’ satisfaction. This study aimed to analyze the effect of compensation, discipline and education and training to employee satisfaction region hospital. This study used survey method. Total population entirely region hospital 136 employees, while the tested sample is 40 respondents. Sampling technique used in this research was purposive sampling. The analytical tool used in this research was multiple linear regression analysis. The results showed that the compensation significant positive effect on job satisfaction, education and training bring significant negative effect on job satisfaction, while discipline was not bring significant positive effect on employee satisfaction in Landak region hospital. Keywords: Compensation, Discipline, Education and Training, and Job Satisfaction.